Wpływ kryzysu gospodarczego na kondycję finansową spółek z sektora transportu publicznego - Tomczak, Sebastian (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2010)
What becomes a very considerable factor in the present period of raging global economic crisis is the risk, especially the one closely related to decisionmaking of various kinds. That risk of assessment as banks or simply by single investors is a case in point. Banks, in order to lessen the risk of not paying off a would-be-granted loan, increase their demands. The aforementioned decisionmaking as such entails the risk. Being in need of such assessment in terms of company’s capacity to continue to operate, different institutions as well as individuals being interested in investing in enterprises employ diverse models that allow of probability estimation of business failure. A series of such methods is referred to as integrated financial analysis of a company (integrated corporate financial analysis). This paper presents five methods of discrimination analysis, applied to assessment of financial situation of the MZK S.A. company in the period of time from 2004 to 2009. the models which deserve special mention are the ones of Polish authorship, along with the two by Altman